Interiors of the 1960s in miniature - Vale, Brenda; Vale, Robert (Architectural History Aotearoa, 2022)
In New Zealand most extant dolls’ houses from the second half of the twentieth century are home-made. The venture by the Auckland firm Jomax into mass-producing a single-storey dolls’ house in the mid-sixties was unusual. This venture may have been spurred on by the traditional two-storey dolls’ houses being produced by the New Zealand Tri-ang factory, also in Auckland. The Jomax "Little Princess" dolls’ house does not, like the New Zealand Tri-ang houses, reflect a UK heritage, but is clearly a New Zealand house similar in form to many being built and published in the 1960s. Jomax also made sets of modern-style furniture suitable for fitting out its four rooms and a hallway. The paper examines the interiors of this New Zealand-designed house and compares them with those of UK (Tri-ang) and East German (Gottschalk) toy houses of the same vintage. The comparison explores the interiors, with their obvious differences and some similarities, and asks whether they reflect the full-scale versions of the time, or whether they were to some extent aspirational.